Randomized trial with soaps - what happens to a newborn baby's skin? - Larissa Habib Mendonça Gois Topan; Vânia Oliveira Carvalho; Kerstin Taniguchi Abagge (Elsevier, 2022)
Objective: Evaluate the effectiveness of a children's soap with physiological pH in maintaining cutaneous pH and moisture of the newborn (NB)'s skin after the first bath. Methods: Randomized, controlled and double-blind clinical trial in a rooming-in of a tertiary maternity hospital in southern Brazil with 204 newborns > 34 gestational weeks. Gestational and obstetric history was evaluated, and newborns were randomized into two groups according to the product applied in the bath: the control group (CG), which used common liquid soap with pH 7.0 and experimental group (EG), which used children's liquid soap with pH 5.8. Evaluation was made immediately before and after bath with skin pH measurement, corneometry and clinical parameters (erythema, scaling and moisture), on the forehead, abdomen and thigh. Results: There was no difference between groups regarding gestational, obstetric and family history (p > 0.05). In CG, skin pH increased in the abdomen and thigh (p < 0.05). In EG there was an improvement in clinical parameters after bathing with: increased moisture, less erythema and less scaling (p < 0.05). On the forehead, there was a significant increase in pH after bathing (p < 0.001) similar in both groups, although no use of soap. There was no difference in corneometry between groups after bathing. Conclusion: Children's liquid soap with physiological pH maintained the acidic skin pH and moisture of the newborn's skin after the first bath, which reinforces the importance of using products with physiological pH in the hygiene of newborns. Registration number RBR-9ky84vd.